2021
DOI: 10.1590/s1678-9946202163049
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial treatment of Corynebacterium striatum invasive infections: a systematic review

Abstract: The aim of this study was to establish an evidence-based guideline for the antibiotic treatment of Corynebacterium striatum infections. Several electronic databases were systematically searched for clinical trials, observational studies or individual cases on patients of any age and gender with systemic inflammatory response syndrome, harboring C. striatum isolated from body fluids or tissues in which it is not normally present. C. striatum h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…A recent systematic review of antimicrobial therapy for C. striatum infections reported 100% susceptibility for included isolates to vancomycin, linezolid, piperacillin/tazobactam, amoxicillin/clavulanate, and cefuroxime. However, the review included a total of 85 individual cases from the literature and reported susceptibilities for only 8 organisms for piperacillin/tazobactam, 3 organisms for amoxicillin/clavulanate, and 2 organisms for cefuroxime [ 15 ]. Reports on C. striatum not included in this review indicate that resistance to these agents may be higher, such as in the above study by Noussair and colleagues [ 14 ] that reported a resistance rate of 66% for piperacillin/tazobactam.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of antimicrobial therapy for C. striatum infections reported 100% susceptibility for included isolates to vancomycin, linezolid, piperacillin/tazobactam, amoxicillin/clavulanate, and cefuroxime. However, the review included a total of 85 individual cases from the literature and reported susceptibilities for only 8 organisms for piperacillin/tazobactam, 3 organisms for amoxicillin/clavulanate, and 2 organisms for cefuroxime [ 15 ]. Reports on C. striatum not included in this review indicate that resistance to these agents may be higher, such as in the above study by Noussair and colleagues [ 14 ] that reported a resistance rate of 66% for piperacillin/tazobactam.…”
Section: Discussionmentioning
confidence: 99%
“…C. striatum is the causative agent of various illnesses, including skin infections such as cellulitis [ 12 ], osteomyelitis [ 13 ], meningitis [ 14 ], pneumonia [ 15 ], bacteremia [ 9 , 16 , 17 , 18 , 19 , 20 ], and infective endocarditis [ 21 ]. Over the past few years, the number of reported cases has been rising due to the increase in the life expectancy of immunosuppressed patients and the improvement in microbiological techniques that are suitable for accurately identifying this microorganism [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of C. striatum from culture is often considered as being contamination unless repeated cultures reveal the same result [ 22 ]. In a recent systematic review, Milosavljevic et al stated the reliability of the Vitek 2 system in the identification of C. striatum after the inclusion of this pathogen in the database [ 3 ], despite the fact that the scientific literature has reported misidentifications when using biochemical methods [ 23 , 24 ]. However, the gold standard technique for C. striatum identification is 16S RNA gene sequencing or, alternatively, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF), due to its simplicity and cost efficiency [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations